2014
DOI: 10.1140/epjc/s10052-014-3216-5
|View full text |Cite
|
Sign up to set email alerts
|

Different critical points of chiral and deconfinement phase transitions in (2 + 1)-dimensional fermion–gauge interacting model

Abstract: Based on the truncated Dyson-Schwinger equations for fermion and massive boson propagators in QED 3 , the fermion chiral condensate and the mass singularities of the fermion propagator via the Schwinger function are investigated. It is shown that the critical point of the chiral phase transition is apparently different from that of the deconfinement phase transition and in Nambu phase the fermion is confined only for small gauge-boson mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…The common critical value means that the chiral symmetry restoration and deconfinement phase transitions are simultaneous. The result is different from that reported in the previous literature [82]. In the case of N f =1, the authors of Ref.…”
Section: Numerical Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…The common critical value means that the chiral symmetry restoration and deconfinement phase transitions are simultaneous. The result is different from that reported in the previous literature [82]. In the case of N f =1, the authors of Ref.…”
Section: Numerical Resultscontrasting
confidence: 87%
“…In the case of N f =1, the authors of Ref. [82] calculated the Schwinger function with Euclidean time in the region from 0 to 600 for different gauge boson mass m a , observed that the logarithm of its absolute value becomes a straight line meaning a stable asymptotic state when the m a exceeds the critical value m c a,de =0.068 that is smaller than the critical value m c a,ch =0.1 for the chiral phase transition and, thus, concluded that the occurrence of the deconfinement phase transition is earlier than the chiral phase transition. Actually, from Fig.…”
Section: Numerical Resultsmentioning
confidence: 99%